ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMA MATERI ALAT INDERA MELALUI MODEL PEMBELAJARAN INQUIRY PICTORIAL RIDDLE - Luzyawati, Lesy (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2017)
This study aims to analyse the critical thinking skills of high school students on five-senses material through the usage of inquiry pictorial riddle learning model. The type of the research used is descriptive quantitative with Pre-Experimental Design and type One-Shot Case Study. The results shows that the students critical thinking ability were vary. Of 32 students, 50% of students can be classified into very good category, 26.5% into good category, and 23.5% students into medium category. The achievement on the five critical thinking indicators of all students were also different, in which the achievement of critical thinking indicator of giving the simplest explanation has the highest percentage of 90% (very good) compared to another indicators, building basic skill has 84% percentage (good), making conclusion 80% (good), and 60% (medium) in giving further information, in which the achievement of this indicator is the lowest compared to another indicator.Â  On indicator of setting strategy and tactics the percentage is 73 (good). Based on the statistical numbers above, the average thinking ability of all students in grade XI MIPA 6 SMA Negeri 1 Sindang Indramayu is 77% wich can be classified into good category.